PERSONNEL ATTENDANCE SYSTEM USING AN IOT-BASED FINGERPRINT (INTERNET OF THINGS) - Stephani Yolanda; Tri Wahyudi sy; Yudi Setyawan; Imam Asrowardi (LPPM STMIK Pringsewu, 2020)
Attendance system in an institution is very important to implement. In fact, an attendance is a gauge of how performance, discipline, job achievement, salary/wages, and productivity of an employee, as well as general progress of the agency. Especially for agencies that have employees of ASN (State civil apparatus), attendance systems must be held to evaluate how ASN responsibilities to the legislation explaining the ASN. Thus, the creation of personnel attendance system using an IOT-based fingerprint (Internet Of Things), is a way of producing an appropriate and effective attendance device for ASN employees in an institution. The attendance device has the advantage of using the fingerprints of each employee in the process of the system, making it very effective to implement. In addition, the attendance process will automatically enter the employee data that does the attendance to the database, then can be accessed by the Web dashboard Using THE media Rest API. The creation of attendance device implements Scrum method, because this method is effectively applied in the creation of group projects. An evaluation of the device's performance was carried out using the SUS (System Usability Scale) method and resulted in a score of 75 out of 31 respondents. The rating is stated in the Good category and is suitable for use based on the results of the evaluation.